Population Screening of Gambling Behavior: Playing to Escape From Problems May Be a Key Characteristic of At-Risk Players - Neophytou, Klavdia; Theodorou, Marios; Theodorou, Christiana; Artemi, Tonia-Flery; Panayiotou, Georgia (Frontiers in Psychiatry, 2021)
The increase of gambling availability and the inclusion of Gambling disorder as an addiction in DSM-5 highlight the importance of brief screening measures aiming to identify at-risk gamblers. The current study, using a brief telephone survey, assessed demographic characteristics and gambling behaviors in 2118 adults. Questions were developed based on DSM-5 criteria for Gambling Disorder, and common assessment tools. A 6% prevalence of as at-risk gamblers was identified. Male gender, low monthly income, high frequency of gambling behavior, large amounts of money spent and gambling to escape from everyday problems or for amusement, specifically for men, were found to be characteristics that can help in the early identification of at-risk gamblers. Gambling for financial gain and as a way to socialize, age, and employment status were not significant predictors of gambling severity. This study shows that the above characteristics can be assessed easily through phone screening of large populations, aiding in prevention practices to reduce the problematic use of gambling activities.